Information audit in electricity utilities: Roles, methodologies, issues and challenges - Ariffin I.; Latif A.A.; Faudzi M.A.; Shariff S.S.; Nadzir M.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Information audit is crucial in understanding the current state of an organisation. By implementing information audit, the needs, the available resources and the gaps are made known to the top management of an organisation, thus helping them to identify steps to be taken to improve the way they manage information in order to stay competitive in their business. Several framework and methodologies were introduced, aimed at providing step by step guidelines to organisations in executing information audit while maximizing the benefits of information audit itself. However, despite the benefits information audit carries, only a minimum number of organisations put information audit into practice and this indicates that current developed framework and methodologies fail to convince organisations to implement information audit. This includes organisations in Electricity Supply Industry (ESI). This paper reviews existing information audit framework and methodologies applicable to ESI and discuses some issues and challenges in implementing information audit based on previous literatuResearch This review is a preliminary study of a research aims at proposing a new improved information audit framework for ESI. © 2014 IEEE.